Association of echocardiographic parameters with mortality in hospitalized patients with lupus nephritis. Issue 11 (17th October 2017) - Chen, Junzhe; Tang, Ying; Zhu, Mingsheng; Lv, Jun; Fu, Sha; He, Huizhen; Zeng, Yuchun; Lin, Cunjie; Xu, Anping
Abstract: Aim: Increasing evidence shows that the cardiac involvement attributes to the mortality of patients with lupus nephritis (LN) and echocardiography provides a valid measurement for cardiac disease. However, the association between echocardiographic parameters and mortality in LN patients without cardiac disease history remains unclear. The aim of this study was to explore the relationship between echocardiographic parameters and the mortality in hospitalized LN patients without cardiac disease history. Methods: A total of 436 LN patients without cardiac disease history who underwent echocardiography at Sun Yat‐sen Memorial Hospital, between 1 January 2000 and 31 December 2014, were enrolled into this study. The association between echocardiographic parameters and all‐cause and cardiac mortality of LN patients was examined by the Cox proportional hazards model. Results: In this cohort study, the median duration of follow‐up was 18 months. Among 436 hospitalized LN patients, 88 patients (20.2%) died. Of them, 38 patients (43.2%) died of cardiac disease. Cardiac symptoms, high systolic blood pressure, high serum levels of C‐reactive protein, low serum albumin, low estimated glomerular filtration rate (eGFR), and decreased left ventricular ejection fraction (LVEF) were found to be independently associated with increased all‐cause mortality. Furthermore, the cardiac symptoms, low eGFR, increased left ventricular mass index (LVMI), and decreased LVEF were independently correlated with an increased cardiac mortality risk. Conclusions: Decreased LVEF was associated with increased all‐cause and cardiac mortality and increased LVMI was an independent risk factor for cardiac mortality in hospitalized LN patients without cardiac disease history. Summary at a Glance: Retrospective cohort study that correlated the echocardiographic findings to outcomes in lupus nephritis. Authors found that a decreased left ventricular ejection fraction and increased left ventricular mass index are correlated independently with all cause mortality.